RUMAH BACA PELANGI IBRAHIMY DALAM UPAYA MENINGKATKAN MINAT BACA ANAK USIA SEKOLAH DI DESA KEDUNGREJO MUNCAR BANYUWANGI - Anis Hidayati MS (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œRumah Baca Pelangi IbrahimyÃƒÂ¢Ã¢â€šÂ¬Ã‚Â is a mini library initiated by Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi students holding internship in 2020 at Kedungrejo Village, Muncar. The target of this program is the school-age children in Kedungrejo Village, Muncar. It is a comfortable and educational public space for school-age children to make them easily obtain sources of reading, knowledge, and insights from provided books, in order to improve readingÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s interest especially the school-age children in this village. Methods used in this program are transparency, accountability, responsibility, independency, and fairness.